2019
DOI: 10.1021/acs.bioconjchem.8b00874
|View full text |Cite
|
Sign up to set email alerts
|

Anchor Peptide-Mediated Surface Immobilization of a Grubbs-Hoveyda-Type Catalyst for Ring-Opening Metathesis Polymerization

Abstract: Adhesion promoting peptides have been reported to enable efficient enzyme immobilization on various material surfaces. Here we report the first immobilization of a synthetic Grubbs-Hoveyda (GH) type catalyst on two different materials (silica and polypropylene). To this end, the GH catalyst was coupled to an engineered (F16C) variant of the adhesion promoting peptide LCI through thiol-maleimide "click" reaction. Immobilization was performed in an oriented manner through the adhesion promoting peptide by simple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 32 publications
0
13
0
2
Order By: Relevance
“…Schwanberg et al coupled the thiolated polypeptide LCI using a Grubbs-Hoveyda (GH) type catalyst 89,90 and mutated the coupled polypeptide LCI to construct a silica material binding element GH1@LCI_F16C. 59 In order to apply the versatility of materials and improve the properties of the material surface, they combined this modified peptide with solid SiO 2 and polypropylene (PP) to make the material both catalytic and hydrophilic. The results showed that the contact angle of SiO 2 after fixation with LCI_F16C was reduced from 59°to 40°.…”
Section: Applications Of Peptides Combined With Inorganic Materialsmentioning
confidence: 99%
“…Schwanberg et al coupled the thiolated polypeptide LCI using a Grubbs-Hoveyda (GH) type catalyst 89,90 and mutated the coupled polypeptide LCI to construct a silica material binding element GH1@LCI_F16C. 59 In order to apply the versatility of materials and improve the properties of the material surface, they combined this modified peptide with solid SiO 2 and polypropylene (PP) to make the material both catalytic and hydrophilic. The results showed that the contact angle of SiO 2 after fixation with LCI_F16C was reduced from 59°to 40°.…”
Section: Applications Of Peptides Combined With Inorganic Materialsmentioning
confidence: 99%
“…Anchor peptides (APs) are short amphiphilic peptides with sizes ranging from 20 to 100 amino acids that bind from aqueous solutions to natural , and synthetic surfaces including metals. , Tailor-made APs are thus applicable in many fields, including biotechnology, catalysis, nanoparticles, medicine, and agriculture …”
Section: Introductionmentioning
confidence: 99%
“…Anchor peptides (APs) are short amphiphilic peptides with sizes ranging from 20 to 100 amino acids that bind from aqueous solutions to natural [9][10] and synthetic surfaces [11][12][13][14] including metals [15][16] . Tailor-made APs are thus applicable in many fields, including biotechnology, 17 catalysis, 18 nanoparticles, 19 medicine, 20 and agriculture 9 .…”
Section: Introductionmentioning
confidence: 99%